An Upconversion Niobium Pentoxide Bulk Glass Codoped with Er3+/Yb3+ Fabricated by Aerodynamic Levitation Method. Issue 6 (23rd March 2015) - Li, Jiaying; Li, Jianqiang; Li, Bo; Yu, Jianding; Qi, Longhao; Lucas, P.
<x xml:space="preserve">Abstract</x> (82−x)NbO2.5–17.4LaO1.5–xZrO2(NLZ) (x = 7.5, 10, 12.5, 15, 17.5, and 20) bulk glasses codoped with Er3+/Yb3+ were successfully fabricated by aerodynamic levitation method for the first time. The structure, thermal stability, and luminescent properties of the samples were investigated systemically by XRD, differential scanning calorimetry, and upconversion spectra. Under 980 nm laser excitation, all samples exhibited green and red upconversion emissions centered at 531, 546, and 674 nm. Results showed that the sample with 15 mol% ZrO2 obtained the most efficient upconversion luminescence and good thermal stability with the glass‐transition temperature as high as 743 °C. The effect of the addition of ZrO2 on the structure behavior and the phonon density in the glass was investigated by Raman spectra, which are the key factors for the upconversion luminescence intensity.